Anti-inflammatory lignans from Melodinus suaveolens. (August 2018) - Fang, Lei; Fang, Zhong-Ying; Zhou, Peng; Bao, Jie; Yu, Jin-Hai; Song, Jin-Tong; Zhou, Jie; Zhang, Hua
Graphical abstract: Highlights: Three new lignans were isolated from the stems of M. suaveolens . New metabolites are rare lignans with a 3, 5-disubstituted C6 unit. Melodinins A and B showed moderate anti-inflammatory activity. Abstract: Three new lignans, melodinins A–C (1 –3 ), together with four known analogues (4 –7 ), were isolated from the stems of Melodinus suaveolens . Their structures including relative configurations were determined by spectroscopic methods, including 1D and 2D NMR, and HRESIMS. Their absolute configurations were unambiguously assigned by electronic circular dichroism (ECD) experiments, especially the application of ECD exciton chirality method. Anti-inflammatory evaluation revealed that compounds 1, 2, 4, and 5 exhibited moderate inhibitory effects on β -glucuronidase release in rat polymorphonuclear leukocytes (PMNs) induced by platelet-activating factor, with IC50 values ranging from 1.68 to 9.56 μM.